2003
DOI: 10.1016/s0092-8674(03)00640-8
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Pyrophosphates Mediate Chemotaxis in Dictyostelium via Pleckstrin Homology Domain-PtdIns(3,4,5)P3 Interactions

Abstract: Inositol phosphates are well-known signaling molecules, whereas the inositol pyrophosphates, such as diphosphoinositol pentakisphosphate (InsP7/IP7) and bis-diphosphoinositol tetrakisphosphate (InsP8/IP8), are less well characterized. We demonstrate physiologic regulation of Dictyostelium chemotaxis by InsP7 mediated by its competition with PtdIns(3,4,5)P3 for binding pleckstrin homology (PH) domain-containing proteins. Chemoattractant stimulation triggers rapid and sustained elevations in InsP7/InsP8 levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
235
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(242 citation statements)
references
References 45 publications
6
235
1
Order By: Relevance
“…Also supporting this model is the recent observation that diphosphoinositol pentakisphosphate (IP 7 ) acts as a negative regulator of chemotaxis in vivo by competing with PIP 3 for binding to PH domains (29). Production of this second messenger is stimulated by cAMP in Dictyostelium, and, interestingly, cells unable to produce IP7 aggregate faster in response to starvation than wild-type cells.…”
Section: Figure 1 Chemotactic Migrationmentioning
confidence: 93%
“…Also supporting this model is the recent observation that diphosphoinositol pentakisphosphate (IP 7 ) acts as a negative regulator of chemotaxis in vivo by competing with PIP 3 for binding to PH domains (29). Production of this second messenger is stimulated by cAMP in Dictyostelium, and, interestingly, cells unable to produce IP7 aggregate faster in response to starvation than wild-type cells.…”
Section: Figure 1 Chemotactic Migrationmentioning
confidence: 93%
“…14,15 Recently, we demonstrated that two inositol phosphates, InsP7 and Ins(1,3,4,5)P4, compete for Akt-PH domain binding with PtdIns(3,4,5)P3 both in vitro and in vivo, providing another level of regulation for Akt membrane translocation and activation. 16,17 In hematopoietic progenitor cells, depletion of Ins(1,3,4,5)P4 by disrupting InsP3KB gene enhances membrane translocation of PtdIns(3,4,5)P3 specific PH domain, thus augments the PtdIns(3,4,5)P3 downstream signals such as Akt. As a result, the phosphorylation of cell cycle inhibitory protein p21 cip1 , a target of Akt, is enhanced, leading to diminished cell cycle inhibitory effect of p21 cip1 .…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modumentioning
confidence: 99%
“…Recently, both PI3K and PTEN have been shown to be required for PI(3,4,5)P 3 production and chemotaxis toward cAMP (11,12). In wild type Dictyostelium cells, the level of PI(3,4,5)P 3 transiently increases within 5 s upon cAMP stimulation and returns to basal levels within 60 s. However, in mutants lacking two of three PI3K genes, the production of PI(3,4,5)P 3 induced by cAMP is dramatically impaired, and the mutant cells are defective in chemotaxis and development (13,14).…”
mentioning
confidence: 99%